Meningkatkan Kreativitas Anak Usia Dini Melalui Metode Bermain Peran - Rapiatunnisa Rapiatunnisa (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2022)
Creativity in children is indicated by independence, confidence, and skills in problem-solving. The pre-research confirmed there are students with immature creativity. This was seen in those who were not confident and did not believe in self-reliance during the learning process. This study aims to determine the extent to which the role playing method can improve the creativity of early childhood at PAUD Nurul Hilal. This study belongs to classroom action research. The subjects of this study were all students of PAUD Nurul Hilal (16 students). The data were collected through the use of tests, observation sheets, and field notes. They were then analyzed by using the P = f/N x 100 to identify the students’ creativity and the P= (post rate - base rate)/ base rate x 100% to clarify the improvement of the students’ creativity. The results show the students’ creativity in the pre-cycle was 24 (30%) “Not good”, the cycle I was 46 (57.5%) “Sufficient”, and 75 (93.75%) “Very good” in cycle II. These infer the role-playing method can improve the students’ creativity of PAUD Nurul Hilal, Sub-district of Batang Tuaka.